Helicobacter infection in pet and food animals: occurrence and zoonotic potential - Wai, Soe Soe; Abdul Aziz, Saleha; Zakaria, Zunita; Hassan, Latiffah; Abu, Jalila (Veterinary Association Malaysia, 2012)
The presence of Helicobacter spp. in the stomach of pet and other animal species has been reported worldwide but the documentation of occurrence of the organism in these animals in Malaysia is lacking. This paper discussed the occurrence of helicobacters in cats and dogs (pet animals) as well as in chickens and pigs (food animals) and the zoonotic potential of these organisms in animals that may infections cause in humans. The occurrence of helicobacters in animals in Malaysia from limited available studies is presented.